Mongolian "Neolithic" and Early Bronze Age ground stone tools from the northern edge of the Gobi Desert. (2016) - , Joan S. Schneider; , Tserendagva Yadmaa; , Thomas C. Hart; , Arlene M. Rosen; Spiro, Annelise
No abstract available